Memahami Hadis Nabi dalam Konteks Kekinian: Studi Living-Hadis - Masrukhin Muhsin (Holistic al-Hadis, 2015)
Living-hadis is the comprehension of hadis under the level of practice. Based on this, the shift of what Fazlur Rahman initiates does not differ all the way around from the study of living-hadis. Such comprehensions reflected in the level of practise, however, in some cases do not correspond with how others understand the hadis in question, but more reflect the contexts of different societies, which is to say, the cotextual comprehension. Any textual and contextual comprehension of hadis which is reflected in the level of practice within any society can be regarded to as living-hadis.